Effect of Habituation to Milking and Natural Suckling on Milking Behaviour and Milk Production Characteristics in Primiparous Sahiwal Cows - Bharti, Pranay; Kamboj, Madan Lal (Indian Journal of Dairy Science, 2019)
The present study was performed to investigate the influence of habituation to milking and natural suckling on milking behaviour and milk production characteristics in primiparous Sahiwal cows. For this experiment 18 late pregnant Sahiwal heifers were selected and divided into 3 groups viz. non-habituated to milking routine and weaned, control (C), habituated to milking routine and weaned (T1) and habituated to milking routine and suckled (T2) group. The mean let-down time (C: 91.48, T1: 82.37, T2: 59.85 sec), milking temperament score (C: 2.11, T1: 1.83, T2: 1.33) and frequency of defecation (C: 0.85, T1: 0.81, T2: 0.62) were significantly (P<0.05) lower in T2 as compared to C and T1 group of cows. The overall means of daily colostrum yield (C: 3.55, T1: 3.85, T2: 4.68 kg/day), daily milk yield (C: 4.82, T1: 5.31, T2: 6.84 kg/day) and milk flow rate (C: 0.595, T1: 0.623, T2: 0.732 kg/min) were significantly (P<0.05) higher in T2 cows as compared to C and T1. The mean plasma cortisol levels after milking were also significantly (P<0.05) higher in case of C group cows followed by T1 and T2 group of cows. It was concluded that the milking behaviour, milk let-down time and milk production performance were improved while stress level reduced in primiparous Sahiwal cows which were habituated to milking routine and allowed natural calf suckling.